Application of Analytical Hierarchy Process Analytical Hierarchy Process Analytical Hierarchy Process Analytical Hierarchy Process Method Method Method Method t tt to Analyze Factors o Analyze Factors o Analyze Factors o Analyze Factors t tt - Dewi, Ika Atsari; Santoso, Imam (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Fishballs increase its popularity recently in Indonesia, following the previously knownproduct which is made up of meat, the meatballs. Fishballs are now mass produced andmay be found in both modern and traditional markets. Like other products, the consistencyof the fishballs quality needs to be established and maintained to meet the marketdemand. The objective of this study was to analyze factors determining the quality ofpackaged fishballs. Factors considered to determine its quality are the raw materials,production process, the products’ chemical and organoleptic characteristics, as well as itspackaging and storage. The Analytical Hierarchy Process (AHP) method and the CriteriumDecision Plus software were used in the study. The results indicated that the quality of flour and mixing process were the mostinfluencing factors to the quality of the packaged fishballs made up of a certain fishspecies. The protein content and the colour of the fishballs may be used as good indicatorsof the product quality. The use of flexible film and low temperature were likely the bestcondition for storage of the packaged fishballs.Keywords: fishballs, Analytical Hierarchy Process, quality